Dual‐Gate GaAs‐Nanowire FET for Room Temperature Charge‐Qubit Operation: A NEGF Approach. Issue 4 (10th February 2023) - Nag Chowdhury, Basudev; Chattopadhyay, Sanatan
Abstract: The performance of dual‐gate GaAs‐nanowire field‐effect‐transistor (FET) is investigated as a charge‐qubit device operating at room temperature. In compatibility with the state‐of‐the‐art classical bit technology, it is shown that the single gate of a nanowire FET can be replaced by two localized gates to achieve such charge‐qubit operation. On application of relevant biases to the localized gates, two voltage tunable quantum dots are created within the nanowire channel with electrostatically controlled single‐state‐occupancy and interdot coupling leading to charge‐qubit operation at room temperature. The associated electron transport is theoretically modeled on the basis of nonequilibrium Green's function formalism. The "initialization" and "manipulation" for qubit operation are performed by applying suitable gate voltages, whereas the "measurement" is executed by applying a small drain bias to obtain a pulse current of ≈pA order. A ≈25 MHz frequency of coherent oscillation is observed for the qubit and a characteristic decay time of ≈ 70 ns is achieved. The results suggest that such dual gate nanowire FET is a promising architecture for charge‐qubit operation at room temperature. Abstract : Electronic qubits, the primary scalable units of quantum information, are currently exhibiting the challenge of ultra‐low operational temperature (≈mK‐µK). The work proposes a dual‐gate GaAs nanowire field‐effect‐transistor based charge‐qubit, designed for room temperature operation, which is possible to fabricate in the state‐of‐the‐art technological route of complementary‐metal‐oxide‐semiconductor (CMOS) processing. Qubit operation: initialization, manipulation, and measurement are described by nonequilibrium Green's function formalism.